PERTIMBANGAN HAKIM TINGKAT BANDING DALAM MENERAPKAN UNSUR-UNSUR PASAL 2 DAN PASAL 3 UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI (Studi Putusan No. 3/TIPIKOR/2016/PT PDG dan No. 9/ TIPIKOR/ 2017/PT PDG) - Rinaldi, Rinaldi; Rosmely, Wirna (UNES Law Review, 2020)
The law governing criminal acts of corruption is Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning Eradication of Corruption. Corruption crime regulated by Law Number 31 of 1999 consists of various forms / types. In writing this thesis, the author conducts research on corruption cases as referred to in decision Number 3 / TIPIKOR / 2016 / PT PDG and Number 9 / TIPIKOR / 2017 / PT PDG. From the results of the study, the first conclusion was obtained that the consideration of the appellate level judges in applying the elements of Article 2 and Article 3, that in Decision Number 3 / TIPIKOR / 2016 / PT PDG, was the legal judgment of the First Level Judge in its decision that could be approved and corroborated by the Level Judge Appeals, except in the case of conviction for the Defendant, according to the Judge of the Level of Appeals the imposed criminal sentence needs to be aggravated and there are still incriminating matters for the Defendant that have not been considered by the First Level Judge. Criminal application by the Court of Appeal Court is to improve the decision of the First Level Court which imprisonment for 2 (two) years and 6 (six) months and improvement of imprisonment for 3 (three) years and a fine of Rp 50,000,000 (fifty) million rupiahs) subsidair criminal confinement for 2 (two) months. Judge's consideration in Decision Number 9 / TIPIKOR / 2017 / PT PDG, is that the Panel of Appeal Judges has considered Article 2 with elements of a criminal offense committed by the defendant. The Appellate Court Judges disagree with the decision of the First Level Court regarding the Acts of the Defendants in violation of Article 3 of Law Number 31 of 1999 concerning Eradication of Corruption. Based on the results of the examination of legal facts in the trial and the consideration of the Panel of Appellate Judges with the Primair indictment proved and fulfilled all elements of Article 2 paragraph (1) Juncto Article 18 paragraph (1) letter b paragraph (2) and paragraph (3) of Law Number 31 of 1999. The application of the criminal sentence dropped to Defendants II and IV for 4 years and fined Rp. 200,000,000.00 (two hundred million rupiah).